Effect of stocking density on pig production - Jin Ho Cho; In Ho Kim (African Journal of Pig Farming, 2017)
Numerous stressors such as environmental, nutritional, pathological or equipment related ones are operative in swine facilities. Among many factors, socking density increases social stress and influences pig performance. Many studies have reported that reducing space allowance could induce decreases in growth performance of pigs. In addition, high stocking density induces a behavioral problem and influences physiological stress during transport. Thus, the optimum stocking density has to be defined for improving pig production.